MUI FATWA AUTHORITY: SOCIAL MOVEMENT TO BOYCOTT ISRAELI PRODUCTS THROUGH INSTAGRAM SOCIAL MEDIA - Aji Mustofa; Fuad Alfikri (UNIVERSITAS SEBELAS MARET (UNS), 2025)
This study analyses the response of Indonesians to MUI fatwa No. 83 of 2023 on the law of supporting the Palestinian cause, specifically the boycott of Israeli products through Instagram. Using a qualitative case study approach with data collection techniques through systematic observation and documentation, this research analyses 20 posts with the highest engagement and around 2,500 comments in November 2023. The theoretical framework integrates Resource Mobilisation Theory, Collective Action Theory, and Digital Activism Theory. The results showed that public responses fell into three categories: pro-fatwa groups that emphasized humanitarian and religious solidarity, contra-fatwa groups that were concerned about economic impacts such as layoffs and losses of small traders, and neutral groups that questioned the clarity of the fatwa. Instagram serves as a discursive space for the dissemination of information on Israel-related products, the articulation of collective Muslim identity in solidarity with Palestine, and the coordination of boycott actions. The ambiguity of MUI's fatwa in mentioning specific brands led to various interpretations and public debates. This research expands the understanding of the transformation of religious authority in the digital era, showing how fatwas are negotiated through digital spaces. This phenomenon reinforces the theory of ‘connective action’ where social media is a channel for collective message dissemination and enables the personalization of resistance narratives and the formation of transnational solidarity.